Participação e representação nos Conselhos Municipais de Educação da região metropolitana de Belo Horizonte - Cynthia Rubia Braga Gontijo (2013)
This thesis Participation and representation in Municipal Boards of Education of the Metropolitan Area in the city of Belo Horizonte is built around the debate on democracy, representation and participation, especially the study of the institutional participatory spaces like Municipal Boards of Education (MBE). Its main objective is to expand current understanding of council representation practices in the MBE of the Metropolitan Area in the city of Belo Horizonte, Brazil (RMBH). Its specific objectives are: a) identify and analyze the trends related to the representation in the MBE from the RMBH, taking into account its functions, attributions and composition; b) get to know the MBE counselors profile and relate it to the meanings those individuals give to their own representation. The feasibility of this analysis is based on a careful examination of the theory about representative and participatory democracy using references of the tensions raised between representation and participation into modernity. Additionally we made a bibliographic and documentary study of institutional educational councils in the Brazilian Republic mainly after its 1988 Constitution which main objective is the understanding of the practices of representation and participation in Brazilian democracy under construction. The empirical research was an investigative and qualitative study about the MBE in 8 municipalities from the RMBH (Belo Horizonte, Betim, Caeté, Contagem, Esmeraldas, Juatuba, Ribeirão das Neves and Sabará). We used primary data from the analysis of the survey and semi-structured interview made with the counselors, and secondary data from those MBE documents. The data suggest that the MBE researched are competent mainly in their technical and pedagogical nature and they were constituted to carry out the consultative, deliberative and normative roles. However some attributions evinced the overlapping of those roles, creating an expansion of competences that mixes the MBE operation with the municipal boards of education work. It is necessary to highlight the detachment of these counselors related to their original segmentation and mostly to society in general. Although those MBE have a democratizating potential besides being part of the participative instances along the continuum between representation and participation, actually they are not fulfilling that possibility. In theory those MBE constitute a continuum of intermediary forms that connect the dimensions of direct and representative democracy, but the framework given by their competences and compositions and the detachment of their represented segments prevent the councils to actually operate as participative spaces and it just emphasizes the distance between representatives and representees.